Effectiveness and safety of the herbal preparation Soveren® in patients with hyperuricemia - Margarita A. Gromova; Vladimir V. Tsurko (ZAO "Consilium Medicum", 2023)
Background. Despite advances in the field of synthetic pharmaceuticals, interest in the use of natural raw materials from representatives of the flora persists throughout the world. Currently, herbal medicine is successfully used in the treatment of both hyperuricemia (HU) and gout. Aim. To evaluate the effectiveness and safety of the herbal preparation Soveren in the prevention and treatment of HU. Materials and methods. The study included 80 patients who were divided into 2 groups: group 1 consisted of patients diagnosed with arthritis with HU (n=40), group 2 patients with gout (n=40). The natural complex of natural origin Soveren was prescribed according to the standard scheme against the background of dietary recommendations. Patients with gout also received urate-lowering therapy. Clinical efficacy and safety of treatment were assessed after 6 and 12 weeks according to the dynamics of laboratory parameters of blood and urine, the EuroQol-5D quality of life questionnaire, assessment of the health status of patients, assessment of patient satisfaction with treatment. Results. The use of the plant complex Soveren in patients with HU does not have a negative effect on the functional state of the liver and kidneys. The drug has a significant positive effect on blood levels, reducing uric acid by 1.5 times, creatinine by 1.11 times, and urea by 1.3 times. In group 2, the addition of the Soveren complex made it possible to achieve the target value of uric acid. In addition, in patients of both groups, within 3 months, the level of total protein in the urine decreased by 3 times, a decrease in the degree of leukocyturia was noted. Against the background of taking the drug in both groups, the relative density of urine increases within the normal range, and a slight acidification of urine was revealed, as well as an increase in urinary excretion of ketones. Most patients positively assessed the result of treatment. Conclusion. Our data confirm the good therapeutic effect and safety of the herbal complex Soveren in patients with HU. With the introduction of the Soveren drug into practice, doctors will have a new effective tool for monitoring the course of HU.